Ray amputation for the treatment of macrodactyly in the foot: report of three cases - Bulut, Mehmet; Karakurt, Lokman; Belhan, Oktay; Serbest, Sancar (Turkish Assoc Orthopaedics Traumatology, 2011)
Foot macrodactyly is a rare congenital anomaly which is characterized by an overgrowth of the soft tissue and bone of the toes. The aim of treatment is to obtain a cosmetic and functional foot. We present three cases of lesser toe macrodactyly on which we performed ray amputation. Postoperative cosmetic and functional results were good in three cases. Ray amputation is a possible surgical treatment that provides good cosmetic and functional results in severe lesser toe macrodactyly.
Keywords: Foot; macrodactyly; ray amputation